2006
DOI: 10.1039/b509277a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and optoelectronic properties of transition metal complexes incorporating dithieno[3,2-b:2′,3′-d]phosphole ligands

Abstract: A series of dithieno[3,2-b:2',3'-d]phosphole-based transition metal complexes, including Au, Fe, Pt, Rh and W as central metals have been synthesised and characterised. Structural investigations by X-ray single crystal crystallography supported the high degree of pi-conjugation in the dithienophosphole ligands. This essential requirement for potential applications in molecular electronics and optoelectronics provides small band gaps for the materials. Investigations toward the optoelectronic properties of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 42 publications
7
62
0
1
Order By: Relevance
“…These results are quite remarkable since it has commonly been observed that oxidation of the phosphorus atom is accompanied by a redshift (Ͻ40 nm) in the absorption and emission spectra. [28] The same is true for transition-metal-complexed phospholes, which undergo a less pronounced bathochromic shift (Ͻ20 nm) [28,30] compared to noncoordinated dithienophospholes. In this case, the very slight changes in the absorption spectra reveal that the oxidation and complexation of the phosphorus atom located at the center of the π-conjugated molecules have almost no effect on the linear absorption properties of the system.…”
Section: Linear (One-photon) Absorption and Emission Spectroscopymentioning
confidence: 57%
See 3 more Smart Citations
“…These results are quite remarkable since it has commonly been observed that oxidation of the phosphorus atom is accompanied by a redshift (Ͻ40 nm) in the absorption and emission spectra. [28] The same is true for transition-metal-complexed phospholes, which undergo a less pronounced bathochromic shift (Ͻ20 nm) [28,30] compared to noncoordinated dithienophospholes. In this case, the very slight changes in the absorption spectra reveal that the oxidation and complexation of the phosphorus atom located at the center of the π-conjugated molecules have almost no effect on the linear absorption properties of the system.…”
Section: Linear (One-photon) Absorption and Emission Spectroscopymentioning
confidence: 57%
“…As mentioned above, it has been demonstrated that 3D branched molecules can potentially lead to synergistic effects by through-space interactions enhancing the TPA features. [17] The intriguing optoelectronic properties demonstrated by dithienophosphole gold complexes in general, [30] encouraged us to use the gold(I) chloride fragment as an out-of-plane unit. Treatment of 3 with Au(THT)Cl (THT = tetrahydrothiophene) at room temperature provided the corresponding donor-acceptor phosphole gold complex 5 in excellent yield (96 %); the characteristic 31 P{ 1 H} NMR signal at δ = 8.9 ppm confirmed its successful formation.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The C−C and P−C bond lengths are similar for both complexes ( Figure 1). The Mo−C CO bonds for cis-CO in 3b range between 2.042(2) and 2.059(2) Å, while the shortest bond is observed for trans-CO (2.012(2) Å), which is in accordance with the stronger M−C CO back-bonding for the trans-CO. 57 17 The tetracarbonyltungsten complex 4c ( Figure 2) shows a distorted-octahedral environment around the tungsten atom with cis-oriented phosphole units. As already discussed for 3b,c, the W−C CO bond for trans-CO (1.990(3) Å) is shorter than that for the cis-COs (2.040(3) Å), indicating that the phosphole is a weaker π-acceptor ligand than the carbonyl groups.…”
Section: ■ Results and Discussionmentioning
confidence: 99%